Public’ Perception, Awareness, Expectations and Experiences towards the Role of Community Pharmacists in Quetta City, Pakistan - Kamran, Kashif; Iqbal, Qaiser; Haider, Sajjad; Anwar, Muhammad; Ishaq, Rabia; Saleem, Fahad (Journal of Pharmacy Practice and Community Medicine)
Aim: The study is aimed to assess public perception, awareness, expectations and experiences towards the role of community pharmacists (CPs) in Quetta City, Pakistan. Methods: This was a questionnairebased, cross-sectional survey. Keeping the aim of the study in mind, a questionnaire was developed by the research team through mutual consensus, experience sharing and extensive literature review. By using an online calculator, 423 respondents were approached conveniently for the data collection. The SPSS v.20.0 was used for data coding and analysis. Based on the objectives of the study, descriptive statistics were applied for data analysis. Results: The mean age of the respondents was 30.61±9.95 and males dominated the group (318, 75.2%). Eighty-one percent of the respondents agreed that CPs provide consultation on how medicine works, identify and prevent errors and are good in explaining things to their level of understanding. Nearly 70% of the respondents expected CPs to take personal responsibility for resolving drug-related problems, to educate them about the appropriate use of medicines and to monitor the response of drug therapy. All respondents were positive when they were asked about their expectations from the CPs. Respondents agreed that CPs are a reliable source of drug information and are important healthcare professionals (80.4 and 77.3% respectively). Counseling was endorsed by 60% of the respondents while CPs were held responsible for resolving drug problems. Conclusion: Although the study findings revealed certain limitations, study respondents had positive attitudes, experiences and constructive expectations towards CPs. The findings also indicated consumer preferences for the evolution of community pharmacist professional services in Pakistan.
Keywords: Public’ perception; Awareness; Expectations; Experiences; Community pharmacist Quetta city; Pakistan